OPTIMIZING THE COMPETITIVENESS OF RETURN ON MUDHÃRABAH TIME DEPOSIT IN IMPROVING PUBLIC INTEREST TO INVEST IN ISLAMIC BANK - Syaparuddin, Syaparuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The aim of this study is to explain the calculation of return on mudhârabah time deposit for the depositors of Islamic banks, and the provision of a fair return to the depositors without leaving any shariah elements. These two issues have become urgent to be discussed in this study, because if their money is deposited in Islamic banks, it will increase the amount of funds available in the Islamic bank, and the amount of funds available directly influence the size of the investment return on Islamic banks. If the results of the large investment, the returns will be obtained by the depositors are also large, and vice versa. In addition, it will also create a sense of calm and peace for themselves, because the money they have deposited in Islamic bank is not only quaranteed by the gorverment but also the system is run in accordance with the shariah of Islam.Â —–Tulisan ini bertujuan untuk menjelaskan perhitungan return deposito mudhârabah bagi deposan di bank syariah, dan pemberian return tersebut secara adil kepada deposan tanpa meninggalkan unsur kesyariahannya. Dua permasalahan ini menjadi urgen untuk dibahas dalam tulisan ini, karena jika uang mereka didepositokan di bank syariah akan meningkatkan jumlah dana yang tersedia di bank syariah tersebut, dan jumlah dana yang tersedia tersebut berpengaruh langsung terhadap besar kecilnya hasil investasi bank syariah. Jika hasil investasi tersebut besar, maka return yang akan diperoleh para deposan juga besar, demikian pula sebaliknya. Selain itu, juga akan menciptakan rasa tenang dan tentram bagi mereka sendiri, karena keberadaan uang mereka tidak saja dijamin oleh pemerintah tetapi juga sistemnya dijalankan sesuai dengan syariat Islam.